The Effects of Self-Esteem and Academic Engagement on University Students’ Performance - Acosta-Gonzaga, Elizabeth (Behavioral sciences, 2023)
The success or failure of a student depends on several factors, including self-esteem, academic engagement, and motivation. Self-esteem and motivation have been found to influence academic engagement, which, in turn, contributes to academic performance. Through a quantitative study, 243 university students were surveyed to analyze the effects of self-esteem and motivation on their academic engagement, which would be reflected in their academic performance. The results show that self-esteem has effects on emotional and behavioral disengagement. Motivation shows greater effects on academic engagement, with metacognitive engagement predicting students’ academic performance. Therefore, promoting metacognitive strategies that help students learn to plan, monitor, and self-regulate their learning will contribute to their performance.